Teasaponin Ameliorates Murine Colitis by Regulating Gut Microbiota and Suppressing the Immune System Response - Yang, Huan; Cai, Rui; Kong, Ziyan; Chen, Ying; Cheng, Chen; Qi, Suhua; Gu, Bing (Frontiers in Medicine, 2020)
Background: Dietary intervention is an exciting topic in current research of inflammatory bowel disease (IBD). The effect of teasaponin (TS) on IBD has not been fully elucidated. Here, we aim to investigate the intestinal anti-inflammatory activity of TS in a dextran sodium sulphate (DSS)-induced colitis mouse model and identify potential mechanisms. Methods: We applied TS to mice with DSS-induced colitis and then monitored the body weight, disease activity index (DAI) daily. When sacrificed, the intestinal permeability was measured. The analysis of mucin and tight junction proteins was conducted. We detected the inflammatory cytokines, the immune cells and related inflammatory signaling pathways. In addition, the gut microbiota were analysed by 16S rRNA sequencing and we also performed fecal microbiota transplantation (FMT). Results: It showed that TS ameliorated the colonic damage by lowering the DAI, prolonging the colon length, reducing inflammatory cytokines and improving the mucus barrier. Parallel to down-regulation of the inflammatory cytokines, the fecal lipocalin 2, p-P65, p-STAT3 and neutrophil accumulation were also decreased in TS-treated mice. Microbiota characterization showed that Campylobacteria, Proteobacteria, Helicobacter and Enterobacteriaceae were the key bacteria associated with IBD. In addition, TS could reverse the Firmicutes/Bacteroidetes (F/B) ratio and increase the beneficial bacteria, including Akkermansia and Bacteroides. TS ameliorated DSS-induced colitis by regulating the gut microbiota, and the gut microbiota could regulate gut inflammation. Conclusions: These studies demonstrated that TS ameliorated murine colitis through the modulation of immune response, mucus barrier and gut microbiota, thus improving gut dysbiosis. In addition, the gut microbiota may play an important role in regulating the host's innate immune system, and the two coexist and are mutually beneficial. We provide a promising perspective on the clinical treatment of IBD.